Clinical significance of respiratory virus detection in patients with acute exacerbation of interstitial lung diseases. (March 2018) - Saraya, Takeshi; Kimura, Hirokazu; Kurai, Daisuke; Tamura, Masaki; Ogawa, Yukari; Mikura, Sunao; Sada, Mitsuru; Oda, Miku; Watanabe, Takayasu; Ohkuma, Kosuke; Inoue, Manami; Honda, Kojiro; et al.
Abstract: Background: The impact of viral infections on acute exacerbations in idiopathic pulmonary fibrosis (IPF) and/or non-IPF interstitial lung disease (ILDs) has been scarcely described. Objectives: To elucidate the frequency of virus infections in patients with IPF or non-IPF ILDs including idiopathic interstitial pneumonia (IIP) or connective tissue disease (CTD)-associated pneumonia, and its influence on their short-term mortality. Methods: We prospectively enrolled adult patients with acute exacerbation of IPF and non-IPF ILDs who were admitted to the hospital during the last 3 years, and examined the respiratory samples obtained from nasopharyngeal, sputum, and bronchoalveolar lavage fluid. Results: A total of 78 patients were identified, consisting of 27 patients with acute exacerbation of IPF and 51 patients with non-IPF ILDs (IIP: n = 27, CTD-associated IP: n = 24). Of all patients, 15 (19.2%) had viruses detected in their respiratory samples including the human herpesvirus 7 (HHV7; n = 4) and cytomegalovirus (CMV) plus HHV7 (n = 3). The proportion of virus infections in the IPF and non-IPF ILDs groups was comparable. The Kaplan-Meier survival curves over 60 days revealed a lower survival probability in the virus positive group (n = 15, 60%) than in the virus negative group (n = 60, 83.3%, p < 0.05). However, the virus infection itself could not predict the 60-day survival probability using simple logistic regression analysis. Conclusions: Viral infections, mostly CMV or HHV7, were identified in both patients with acute exacerbation of IPF and non-IPF ILDs, but the clinical significance on short-term mortality or isolation itself from respiratory samples remains to be determined.